Natural Resource Management Strategy as a Leverage for the Tourism Sector in Ngalanggeran Gunung Kidul Regency - Fahmi Fahrudin Fadirubun; Agus Sutedjo; Ketut Prasetyo; Muzayanah; Dian Ayu Larasati (Technium Social Sciences Journal, 2023)
Nglanggeran Village is a village located in Gunung Kidul Regency, which is precisely in Patuk District, D.I Yogyakarta Province. Nglanggeran Village is a that has enormous potential, both natural resource potential andtourism potential. The method used is the descriptive method in which we look at an area under study and describe the events or circumstances that exist. The purpose of this research is to find out the strategies that willbe carried out in empowering natural resources which also affect the tourism potential in the Nglanggeran Village and can advance the economic growth of residents around the village. Before becoming an ecotourismvillage, the ancient volcanic area of Nglanggeran was an arid area. In the past, people often took rocks and cuttrees from the area to sell, this could cause environmental damage. Karang Taruna of Nglanggeran Village realizes that if this condition continues, it will have a negative impact on the lives of the surrounding community. From this, Karang Taruna then changed the condition of the ancient volcano into an attractive area and could provide benefits for the community.